Defibrotide Inhibits Platelet Activation by Cathepsin G Released From Stimulated Polymorphonuclear Leukocytes - Evangelista, Virgilio; Piccardoni, Paola; Gaetano, Giovanni de; Cerletti, Chiara (Thrombosis and Haemostasis, 1992)
Defibrotide is a polydeoxyribonucleotide with antithrombotic effects in experimental animal models. Most of the actions of this drug have been observed in in vivo test models but no effects have been reported in in vitro systems. In this paper we demonstrate that defibrotide interferes with polymorphonuclear leukocyte-induced human platelet activation in vitro. This effect was not related to any direct interaction with polymorphonuclear leukocytes or platelets, but was due to the inhibition of cathepsin G, the main biochemical mediator of this cell-cell cooperation. Since cathepsin G not only induces platelet activation but also affects some endothelial cell functions, the anticathepsin G activity of defibrotide could help to explain the antithrombotic effect of this drug.